(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article explores the implementation of procedures in the state language within organizations, emphasizing the pivotal role of digital technology in facilitating effective communication and compliance. As globalization and technological advancements reshape operational frameworks, ensuring the linguistic alignment of organizational procedures has become crucial for organizational integrity, employee engagement, and regulatory adherence. The research examines various digital tools and platforms that enhance the translation, dissemination, and enforcement of procedures in the state language, providing case studies from sectors such as public administration, education, and corporate businesses. Ultimately, the findings highlight best practices and strategic recommendations for organizations aiming to foster a bilingual or multilingual workplace while maintaining organizational efficacy.